Effectiveness of MOPS-F Training to Enhance Parental Understanding of Analytical Thinking Stimulation in Children Aged 3-6 Years - Maula, Maizan Rahmah; Salim, Rose Mini Agoes (Jurnal Pendidikan Progresif, 2025)
Effectiveness of MOPS-F Training to Enhance Parental Understanding of Analytical Thinking Stimulation in Children Aged 3-6 Years. The ability to think analytically is one of the important abilities for early childhood. Early childhood who is not yet independent, has not been able to solve their daily problems, and frequent tantrums are examples of children who have not been stimulated their analytical thinking skills. Parents, who are the closest environment, are the most influential factor in early childhood development. Objective: This study aims to test the effectiveness of MOPS-F training to improve parents' understanding of the stimulation of analytical thinking skills of children aged 3-6 years. Methods: The intervention carried out in this study was in the form of experiential learning training consisting of 4 stages. In the concrete experience stage, parents are invited to experience new experiences, then in the reflective observation stage, parents are invited to reflect and discuss, in the abstract conceptualization stage, the researcher provides material to form concepts, and finally at the active experimentation stage, parents apply new knowledge to real action. The study was conducted on 50 parents of early childhood. The material provided included understanding the importance of stimulating analytical thinking and how to stimulate children with the MOPS-F method. The measurement instrument used in this study was 10 questions related to the MOPS-F training module prepared by the researcher. This study was analyzed using the Wilcoxon Signed-Rank test. Findings: The results showed that MOPS-F training was able to improve parents' understanding of children's stimulation of analytical thinking (W=1275, p-value<.001). Conclusion: Experiential learning training is a method that is suitable for adult learning processes. Parents are the most influential environment in early childhood development, therefore, training carried out on early childhood parents is very important to support children's development, especially in stimulating their analytical thinking skills. This research can be useful to be a foundation in the preparation of the next intervention in parents of early childhood. Keywords: stimulation, early childhood, analytical thinking, stimulation methods, parental training.